Peningkatan prestasi siswa materi kebebasan berorganisasi PKn - Tiono Tiono (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Nahdlatul Ulama Blitar, 2023)
The aims of this research are: (1) to describe the effect of Cooperative Script learning on Citizenship Education learning outcomes. (2) Describe how far the understanding and mastery of Citizenship Education subjects after the implementation of Cooperative Script learning. This study used three rounds of action research. Each round consists of four stages: design, activity and observation, reflection, and revision. The target of this research was students of Class V Semester II at SDN Medowo 2, Kandangan District, Kediri Regency for the 2018/2019 academic year. The data obtained is in the form of evaluation results, observation sheets of teaching and learning activities. From the results of the analysis it was found that student achievement increased from cycle I to cycle III, namely, cycle I 64.00%, cycle II 80.00%, cycle III 100%. The conclusions from this study are that the Cooperative Script method can have a positive effect on the learning motivation of Class V students, and this learning model can be used as an alternative to learning Citizenship Education.